Analysis of The EOG Signal Differences Based on Electrode Placement as Referred to by The Display on Delphi - Habibie, Muhammad Burhanudin; Nur Hudha Wijaya; Wisnu Kusuma Wardana (Medika Teknika : Jurnal Teknik Elektromedik Indonesia, 2025)
Human eyes have different movement patterns, which can be analyzed through various movements. Biopotential signals are electrooculogram signals, which are electrical signals derived from eye muscle movements. The device to record these signals is Electrooculography (EOG). Eyes can be modeled as having a positive pole on the cornea and a negative pole on the retina. The electrical signals measurable from eye activity are referred to as EOG. The comparative test of reference electrode placement unveiled value differences between the placement of the reference electrodes on the forehead and the neck. In the eye conditions of still, up, and down, the electrodes on the neck depicted higher values than those on the forehead, while in the right and left eye conditions, the electrodes on the forehead yielded greater values than those on the neck.